Tracking international aid projects for ocean conservation and climate action - Nagisa Shiiba; Miko Maekawa; Tibor Vegh; John Virdin (Asian Development Bank Institute (ADBI), 2022)
Ocean conservation and sustainable use cannot be pursued or achieved without consideration of the planetary impacts of climate change, and particularly the role of the oceans in both mitigation and adaptation. For this reason, the international community has increasingly committed to providing aid to help finance public goods for ocean conservation and climate action. Although many organizations have set up mechanisms to track both aid and climate finance, such trackers are usually not focused on financial flows related to ocean conservation and climate action. In the absence of such coordinated tracking and monitoring of aid, policymakers cannot assess the attention or priority of international funding mechanisms on oceans and ocean-related climate issues. As such, the purpose of this study is to contribute to efforts to track aid for ocean conservation and climate action by providing a comprehensive baseline of international flows, by relevant global goal and target. We will build upon recent efforts that have established a baseline for international institutions operating at the global level. According to the data collected, we estimate that the cumulative public financing for ocean conservation and climate action grew from USD579 million in 2013 to over USD3.5 billion in 2019.
Keywords: F35; H84; Q54; F64; 330; ocean financing; sustainability and climate change; international aid